Dose-dependent changes in real-life affective well-being in healthy community-based individuals with mild to moderate childhood trauma exposure - Berhe, Oksana; Mößnang, Carolin Ulrike; Reichert, Markus; Ma, Ren; Höflich, Anna; Tesarz, Jonas; Heim, Christine M.; Ebner-Priemer, Ulrich; Meyer-Lindenberg, Andreas; Tost, Heike (Borderline Personality Disorder and Emotion Dysregulation, 2023)
Childhood trauma exposures (CTEs) are frequent, well-established risk factor for the development of psychopathology. However, knowledge of the effects of CTEs in healthy individuals in a real life context, which is crucial for early detection and prevention of mental disorders, is incomplete. Here, we use ecological momentary assessment (EMA) to investigate CTE load-dependent changes in daily-life affective well-being and psychosocial risk profile in n = 351 healthy, clinically asymptomatic, adults from the community with mild to moderate CTE.